Peningkatan Produksi Pengrajin Batu Bata Melalui Perbaikan Proses Pencetakan - Muhammad, Abdul Kadir; Arsyad, Muhammad; Anzarih, A.M. (INTEK: Jurnal Penelitian, 2017)
The purpose of this study is to improve theproduction process of brick craftsmen. Brick production processconsists of four stages: printing, drying, burning, and cooling. Ofthe four stages, which will be completed in this research is theprocess of printing bricks. The printing process still uses simpleequipment that is a rectangular wooden beam with a size of 20cm x 10 cm x 5 cm. The printing process includes: preparation ofraw materials by hoeing the soil, making the dough by tramplingto the shape of a paste, printing using a printing tool. For thismethod, for 4 people craftsmen can print bricks as much as 2,000pieces / day (8 hours work / day). The number of bricks is idealfor once combustion of 40,000 pieces. For reach that amount ittakes 20 days. The method applied in improving the productionprocess of brick craftsmen is the application of brick machine.The operation of the brick printing machine requires 4 personswith their respective functions: 1 person to insert the soil into theprinting machine, 1 person to cut the brick bar, 1 person to movethe bricks from the printing machine, 1 person to bring thebricks to the drying place. Based on the result of the test, it isconcluded that by using the brick machine, the dough making iseasier and shorter, the production capacity increased to 6,780bricks / day, the time required for the production of 40,000 piecesof bricks is 6 days.